Complete solar thermal direct reduction of iron ore by hydrogen in a particle-fed reactor under concentrated sunlight - Stéphane Abanades; R. F. Naranjo Garcia; Srirat Chuayboon (Resources Chemicals and Materials, 2025)
• Solar thermal iron ore direct reduction with H 2 enhances ironmaking sustainability • A particle-fed rotary kiln with ceramic cavities yielded high conversion performance • A rotating cavity made of BN promoted particle flowability and continuous extraction • Particle reduction approaching completion was achieved in semi-continuous operation mode • Pure Fe sponge products formation collected at the reactor outlet was confirmed Solar iron production from H 2 -based direct reduction of iron ore was investigated in a continuously particle-fed reactor for performance analysis. Concentrated solar energy was used as the external source of high-temperature process heat and hydrogen was used as reductant, thereby enabling decarbonation of the iron-making process. The solar reactor featured a rotary kiln composed of a refractory conical cavity, in which the reacting particles were injected and extracted under a flow of H 2 reductant, subjected to real concentrated solar irradiation. The reactor was experimentally tested under both continuous and semi-continuous operation modes to determine and compare the key performance metrics. The on-sun experiments focused on unraveling the effect of the cavity material and operating mode on the process performance including H 2 consumption, particle conversion and iron product purity. A cavity made of mullite appeared unfavorable for continuous particle flow due to agglomeration and adherence to the walls. Conversely, boron nitride promoted particle flowability while totally eliminating adhesion to the walls. In continuous mode, the conversion was kinetically limited due to a low particle residence time in the cavity. Semi-continuous operation was thus tested with cavity rotation turned off during injection and rotation turned on for particles extraction, which warranted a high-enough reaction duration with particle conversion approaching completion. Maximum conversion up to 99% was achieved with complete recovery yield of the converted product at the reactor outlet. Characterization of solid products (XRD, SEM) confirmed the successful production of pure sponge iron. Further scaling-up of the solar reactor concept with longer cavity length will enhance the particle residence time, thereby favoring their conversion in continuous mode.
Keywords: Chemical Looping and Thermochemical Processes; Iron and Steelmaking Processes; Iron oxide chemistry and applications